Comparison of Leptin and Tnf-Α Levels in Type 2 Diabetes Mellitus Patients with and Without Obesity - Abdulloh ABBAS; Lisyani B. SUROMO; Meita HENDRIANINGTYAS; Nyoman Suci WIDYASTIT; Dwi RETNONINGRUM; Luluk CAHYANTI (Modern Medicine)
Background: Leptin and tumor necrosis factor alpha (TNF-α) are the main adipokine products of adipose tissue, leptin is a hormone that controls appetite, while TNF-α acts as a proinflammatory cytokine that can cause Insulin resistance Leptin and TNF-α levels are influenced by body mass index (BMI). Objective: To prove the differences in leptin and TNF-α levels between T2DM patients with and without obesity. Material and Method: A cross-sectional study was conducted on 31 T2DM subjects with obesity and 29 DMT2 subjects without obesity. Leptin and TNF-α levels were measured using the enzyme linked immunosorbent assay (ELISA) method. Obesity status was determined based on BMI values where BMI ≥25 kg / m2 was the obesity group and BMI <25 kg / m2 group without obesity. The t-test was used as the comparative test. Results: The median leptin levels in the obese and non-obese T2DM groups were 31.8(7;74.6) ng/mL and 9.2(0.8;36.7) ng/mL. There was a difference in leptin levels between the two groups with p=0.001. The median TNF-α levels in the obese and non-obese DMT2 group were 6.6(2.2;21.2) pg/mL, and 4.4(1.6;15.8) pg/mL. There was a difference in TNF-α levels between the two groups with p=0.007. Conclusion: There are significant differences in leptin and TNF-α levels between T2DM patients with and without obesity, where leptin and TNF-α levels are higher in T2DM patients with obesity than T2DM patients without obesity.